Note: Microcomputer Performance of “FABLE” on Hoffmann's Data Sets - Johnson, Roger V. (Management Science, 1993)
Some of the legitimacy of Hoffmann's (1992) Eureka is gained from his statement that “Eureka … would seem to be approximately six times as fast (as Johnson's (1988) FABLE on the literature set). However, Eureka had one problem for which its solution was one station over the optimal, whereas FABLE's solutions were all optimal.”